Apuntes para una política de investigación lingüística en el Perú - Quesada, Félix (1987)
Currently in our environment there is a lack of a linguistic research policy that guides and promotes linguistic studies, with a view to both regional and national development and the development of the discipline itself. A policy of this nature must provide for the prioritization of the types of studies and the rationalization of resources in such a way that they are used to support research projects that are aimed at elucidating the problems of national groups in the various regions of the world. country and, at the same time, present alternatives to face them. The purpose of this paper is to offer for discussion some ideas that we believe constitute the basis of a linguistic research policy that aspires to respond to the complex socio-linguistic reality of Peru.